Dambreak Risk Analysis of Jenelata Dam and its Mitigation Plan - Calvin Sandi; Eka Oktarianto Nugroho; M. Cahyono (Bulletin of Civil Engineering, 2022)
Makassar City is often experiences flood during rainy season and lack of water during dry season. Therefore, Jenelata Dam is planned to be built in South Sulawesi with a watershed area of 221.22 km2. Every dam has a dambreak potential due to many factors such as earthquakes. Â Risk analysis is carried out in order to study the most effective mitigation plan on minimizing the risk index. Flood hydrograph modeling due to dambreak is done using HEC-HMS with the most extreme dambreak scenario is due to overtopping with a discharge peak of 48726.47 m3/s. The flood inundation modeling is done using HEC-RAS with the inundation area due to overtopping was 20842.48 Ha. The results of the inundation map and demographic data are then used as the basis for determining the risk index per sub-district. The mitigation plan is in the form of structural and non-structural. The structural solution was determined through testing the effectiveness of every solution on reducing the flood inundation area, where the installation of embankments with 150 cm high on the main and river branch give the best result. Implementation of the mitigation plan is based on the risk index value of the sub-district and its components. The final result is a risk index with implementation of the mitigation plan as a comparison to the risk index without the mitigation plan. The result obtained is a decrease in the risk index on several sub-districts from high to medium or medium to low.Â